I see, I think I wonder: An evaluation of journaling as a critical reflective practice tool for aiding teachers in challenging or confronting contexts - Lowe, G.; Prout, P.; Murcia, Karen (Edith Cowan University, 2013)
In October 2011, five selected Western Australian teachers took part in a teacher mentoring project in Tanzania. The teachers spent a month embedded in local primary and secondary schools, working collaboratively with their Tanzanian counterparts. As a strategy for making sense of their experiences, each teacher was asked to maintain a reflective journal, using the Harvard Visible Thinking Routine of 'see, think, wonder' as a critical structure for guiding their journal writing. The purpose of this article is to discuss the effectiveness of journaling for teachers in challenging teaching situations, and the usefulness of the Harvard approach in structuring the reflective process as part of an action-based reflective model. As such, the article examines not just the role of critical journaling in helping the participating teachers make sense of their African experience, but the potential of this approach in general in helping teachers faced with challenging or confronting teaching contexts.